Capital Punishment in the United States, 1973-2003 ([Verlag nicht ermittelbar], 2006)
This data collection provides annual data on prisoners under a sentence of death and prisoners whose offense sentences were commuted or vacated during the period 1973-2003. Information is supplied for basic sociodemographic characteristics such as age, sex, education, and state of incarceration. Criminal history data include prior felony convictions for criminal homicide and legal status at the time of the capital offense. Additional information is available for inmates removed from death row by year-end 2003 and for inmates who were executed.